Estimating the association between being seropositive for cysticercosis and the prevalence of epilepsy and severe chronic headaches in 60 villages of rural Burkina Faso. - Ida Sahlu; Hélène Carabin; Rasmané Ganaba; Pierre-Marie Preux; Assana Kone Cissé; Zekiba Tarnagda; Sarah Gabriël; Veronique Dermauw; Pierre Dorny; Cici Bauer; Athanase Millogo (Public Library of Science (PLoS), 2019)
BACKGROUND:Individuals diagnosed with neurocysticercosis often present with epilepsy and sometimes with progressively worsening severe chronic headaches (WSCH). While cross-sectional associations between seropositivity to cysticercal antigens and epilepsy have been reported, few large scale studies have been conducted in West Africa and none have measured the association between seropositivity to cysticercal antigens and headaches. This study aimed at filling these knowledge gaps by estimating the strength of the cross-sectional association between seropositivity to cysticercal antigens and the prevalence of epilepsy and WSCH in 60 villages of Burkina Faso, West Africa. METHODOLOGY/PRINCIPAL FINDINGS:Baseline data from a cluster randomized controlled trial collected from January 2011 to February 2012 in 60 villages across three provinces in Burkina Faso were used. Between 78 and 80 individuals were screened for epilepsy and WSCH in each village, and those screened positive were confirmed by a physician. Seventy-five percent of all participants were asked to provide a blood sample to test for Taenia solium cysticercus circulating antigens. Hierarchical multivariable logistic models were used to measure the association between seropositivity to cysticercal antigens and epilepsy (lifetime and active) as well as WSCH. Among 3696 individuals who provided a blood sample, 145 were found to have epilepsy only, 140 WSCH only and 19 both. There were positive associations between seropositivity to cysticercal antigens and active epilepsy (prevalence odds ratio (POR): 2.40 (95%CI: 1.15-5.00)) and WSCH (POR: 2.59 (1.34-4.99)). CONCLUSIONS/SIGNIFICANCE:Our study is the first to demonstrate a cross-sectional association between seropositivity to cysticercal antigens and WSCH in a large community-based study conducted in West Africa. The measured cross-sectional association had a strength similar to the ones previously observed between seropositivity to cysticercal antigens and lifetime or active epilepsy. As a result, preventing new cysticercosis cases in communities may reduce the prevalence of these two important neurological disorders.